Developments of 3D Printing Microfluidics and Applications in Chemistry and Biology: a Review - He, Yong; Wu, Yan; Fu, Jian-zhong; Gao, Qing; Qiu, Jing-jiang (Electroanalysis (New York, N.Y.), 2016)
Three‐dimensional (3D) printing, also called additive manufacturing (AM) or rapid prototyping (RP), is a layer by layer manufacturing method and now has been widely used in many areas such as organ printing, aerospace and industrial design. Now 3D printed microfluidics attract more and more interests for its rapid printing in the lab. In this review, we focused on the advances of 3D printed microfluidic chips especially the use in the chemistry and biology (vascularization and organs on chips). Based on the brief review of different 3D printing methods, we discussed how to choose the suitable 3D printing methods to print the desired microfluidics. We predict that microfluidics will be evolved from 2D chips to 3D cubes, printed hydrogel‐based microfluidics will be reported and widely used, sensors & actuators could be integrated in the microfluidics during printing, and rapid assembling chips with printed microfluidic modules will be popular in the near future.